2022
DOI: 10.1186/s12905-022-02018-z
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of and adherence to oral pre-exposure prophylaxis among adolescent girls and young women at high risk of HIV-infection in Kampala, Uganda: A qualitative study of experiences, facilitators and barriers

Abstract: Background There is limited information on factors that influence oral pre-exposure prophylaxis (PrEP) uptake and adherence among adolescent girls and young women (AGYW). We conducted a qualitative methods study to explore experiences, facilitators and barriers of PrEP uptake and adherence to PrEP among AGYW at risk of Human Immunodeficiency Virus (HIV) infection in Kampala, Uganda. Methods This study was nested in a prospective cohort study that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
(49 reference statements)
3
13
0
Order By: Relevance
“…End-user research with potential DPP users, providers and male partners found that side effects are one of the largest concerns of both prospective DPP clients and providers ( 56 ), which could have implications for user acceptability and provider willingness to offer the DPP. For both COC and oral PrEP, the provision of information on side effects and how to manage them improves outcomes and continued use ( 46 , 57 , 58 ). Counseling users to understand potential changes to bleeding patterns is key to user satisfaction and continuation with other FP methods ( 59 , 60 ), and by extension, is expected to be critical to effective use of the DPP.…”
Section: Discussionmentioning
confidence: 99%
“…End-user research with potential DPP users, providers and male partners found that side effects are one of the largest concerns of both prospective DPP clients and providers ( 56 ), which could have implications for user acceptability and provider willingness to offer the DPP. For both COC and oral PrEP, the provision of information on side effects and how to manage them improves outcomes and continued use ( 46 , 57 , 58 ). Counseling users to understand potential changes to bleeding patterns is key to user satisfaction and continuation with other FP methods ( 59 , 60 ), and by extension, is expected to be critical to effective use of the DPP.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of mobility's effects ranges widely—in part because definitions of mobility are so varied—from a 47% reduction in viral suppression to a six‐fold reduction in 1‐year retention. Mobile people are also less likely to be retained in pre‐exposure prophylaxis (PrEP) programmes [ 41 , 42 ]. Several qualitative studies from diverse settings, including West, East and Southern Africa, demonstrate how mobility can trigger a chain of events leading to treatment interruption [ 13 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Myths and misconceptions about PrEP and other attributes of PrEP such as the daily dosing and routine screening and medication monitoring may affect interest and willingness in PrEP among these populations. 8,11,26,27 However, it is not clear why lack of interest was highest among MSM, considering the high risk of transmission associated with anal sex, particularly receptive anal intercourse. 28 Further studies are needed to better understand this result.…”
Section: Discussionmentioning
confidence: 99%